Effect of strip width in maize/peanut intercropping on water use efficiency - Sun, Xianglong; Zhang, Yongyong; Zhang, Shihang; Yang, Ning; Xia, Guimin; Feng, Liangshan (Frontiers in Sustainable Food Systems, 2025)
IntroductionMaize and peanut intercropping can optimize allocation of rainfall through crop canopies, enhancing crop resilience to drought. However, the mechanisms underlying this process remain unclear.MethodsThis study investigates the impact of strip width on rainfall redistribution to the soil in maize (MS) and peanut (PS) monoculture systems, as well as in intercropping systems with strip configurations of 2:2 (M2P2), 4:4 (M4P4), and 8:8 (M8P8).Results and discussionResults showed that maize/peanut intercropping consistently improved system water use efficiency (WUE) over the three-year experiment, with the M4P4 treatment maintaining the highest WUE throughout. Strip width significantly influenced stemflow and throughfall in maize rows, as well as throughfall in peanut rows, with maize plant height and leaf area playing key roles. Among the 17 rainfall events studied, maize rows in the M2P2, M4P4, and M8P8 treatments obtained 17.4%, 10.8%, and 5.4% more rainfall, respectively, compared to the MS. However, compared to PS, water captured by intercropped peanut rows decreased by 20.6%, 13.2%, and 7.1%, respectively. An edge effect was observed in the intercropping treatments, with stemflow in maize rows increasing by 23.7%, 17.8%, and 14.6%, and throughfall by 12.2% (M2P2), 10.6% (M4P4), and 8.6% (M8P8) compared to MS. Conversely, the M2P2, M4P4, and M8P8 treatments decreased throughfall in peanut by 20.6%, 18.0%, and 16.0%, respectively, compared with PS. Overall, our findings suggest that optimizing strip width in intercropping systems can improve both crop productivity and water management, offering insights for sustainable agricultural practices in regions with limited water resources.